1)
[tex]a) \\\\|3x+2|=7\\\\3x+2=7\\3x=7-2\\3x=5 /:3\\x=\frac53\\\\-(3x+2)=7\\-3x-2=7\\-3x=7+2\\-3x=9 /:(-3)\\x=\frac{9}{-3}\\x=-3\\\\x = \frac53 \text{ lub } x=-3[/tex]
[tex]b) \\|\frac{1-x}2|=3\\\\\frac{1-x}2=3 /*2\\1-x=6\\-x=6-1\\-x=5 /*(-1)\\x=-5\\\\-(\frac{1-x}2)=3\\\frac{-1+x}2=3 /*2\\-1+x=6\\x=6+1\\x=7\\\\x=-5 \text{ lub } x=7[/tex]
[tex]c) \\\\2*|x-3|=8\\\\2*(x-3)=8\\2x-6=8\\2x=8+6\\2x=14/:2\\x=7\\\\2*(-1)*(x-3)=8\\2*(-x+3)=8\\-2x+6=8\\-2x=8-6\\-2x=2 /:(-2)\\x=-1\\\\x=7 \text{ lub } x=-1[/tex]
[tex]d) \\\\7+|3y|=9\\\\7+3y=9\\3y=9-7\\3y=2/:3\\y=\frac23\\\\7+(-3y)=9\\7-3y=9\\-3y=9-7\\-3y=2 /:(-3)\\y=-\frac23\\\\y=\frac23 \text{ lub } y=-\frac23[/tex]
[tex]e)\\\\3*|1-2w|-6=0\\\\3*(1-2w)-6=0\\3-6w-6=0\\-6w=-3+6\\-6w=3 /:(-6)\\w=-\frac36\\w=-\frac12\\\\3*(-1)*(1-2w)-6=0\\3*(-1+2w)-6=0\\-3+6w-6=0\\6w=3+6\\6w=9 /:6\\w=\frac96\\w=1\frac36\\w=1\frac12\\\\w=-\frac13 \text{ lub } w=1\frac12[/tex]
[tex]f) \\\\5-|4-x|=5\\\\5-(4-x)=5\\5-4+x=5\\x=5-5+4\\x=4\\\\5-(-1)*(4-x)=5\\5-(-4+x)=5\\5+4-x=5\\-x=5-5-4\\-x=-4\\x=4\\\\x=4[/tex]